C05 A novel BACHD transgenic rat exhibits characteristic neuropathological features of Huntington disease. (29th August 2012) - Yu, L; Parwez, EP; Osmand, AP; Redensek, A; Metzger, S; Clemens, LE; Park, L; Howland, D; Calaminus, C; Gu, X; Pichlern, B; Yang, XW; et al.
Abstract : Background: Huntington disease (HD) is an inherited progressive neurodegenerative disorder, characterised by motor, cognitive and psychiatric deficits as well as neurodegeneration and brain atrophy beginning in the striatum and the cortex and extending to other subcortical brain regions. The genetic cause is an expansion of the CAG repeat stretch in the HTT gene encoding huntingtin protein (htt). Methods: Here, we generated and characterised a HD transgenic rat model using a human bacterial artificial chromosome (BAC) which contains the full-length HTT genomic sequence with 97 CAG/CAA repeats and all regulatory elements. Results: BACHD transgenic rats display a robust, early-onset and progressive HD-like phenotype including motor deficits and anxiety-related symptoms. The phenotype is characterised by striatal dysfunction associated with an imbalance in the striosome and matrix compartments in early stages of the disease. This was, in addition to reduced dopamine receptor binding, readily detectable by in vivo imaging. Neuropathologically, the distribution of neuropil aggregates and nuclear accumulations of N-terminal mutant huntingtin in BACHD rats is similar to that seen in HD patients. Neuropil aggregates in the sensorimotor circuit may be associated with motor dysfunction and aggregates in the limbic-based circuits could be related to anxiety changes and thus render this model suitable for the ongoing research in how these circuits are affected in HD. Conclusion: Taken together, our data demonstrate that this transgenic BACHD rat line may be a valuable model for further understanding the disease mechanisms and for preclinical pharmacological studies.